Effects of fungal treatment on rice straw digestibility and rumen methane mitigation - Pauzi, Mohd Azlan (2015)
Rice straw is a major global agro-byproduct with about 90% are produced in Asia. Although some of this agro-byproduct is used as roughage source for ruminant livestock, its low nutritive value and high non-digestible fibre contents limit its use. In addition, fermentation of high fibre diet in the rumen is accompanied by high rate of enteric methane production, which in return causes 7-10 % of the dietary energy loss. Enteric methane production from ruminants contributes about 33-39 % of total methane, a greenhouse gas, from agricultural sector which has been implicated as a major cause of global warming and climate change. Improving the nutritive value of agro-byproduct such as rice straw will allow it to break down quickly, thus reduces its retention time in the rumen and lowers its contribution on methane production. Nutritive values of lignocellulosic materials could be improved by biological treatment using fungi. A recent laboratory study in Universiti Putra Malaysia reported that Aspergillus terreus (ATCC 74135) can effectively breakdown lignocellulose component of rice straw and also produce lovastatin which has the potential to mitigate methane production in vitro. Thus, the primary objective of this follow-up study was to evaluate the effects of fungal treatment on rice straw digestibility and methane mitigation in vitro and in vivo in goats. The objective of the first experiment (Chapter 3) was to develop an up-scale laboratory protocol to treat rice straw with Aspergillus terreus (ATCC 74135) to achieve an optimized balance in reduction of lignocellulose content and production of lovastatin in the treated rice straw using solid state fermentation (SSF). The treatments consisted of 12 combinations of three levels (amount) of rice straw (300, 600 and 900 g) and four incubation durations (8, 10, 12 and 14 days) incubated at 25°C, 50% moisture and pH at 6. Untreated rice straw was used as control to compare with the treatment effects. The result showed that all treatments reduced the lignocellulose contents compared to control with hemicellulose content by 7.6 to 26.4% and cellulose content by 4.6 to 21.6%, depending on the treatment. T1 (300 g x 8 days), T2 (300 g x 10 days), T7 (600 g x 12 days) and T8 (600 g x 14 days) produced significantly higher amount of lovastatin (P<0.05) than the other treatments, thus the above four treatments were selected for further testing in the second experiment. The second experiment (Chapter 4) was conducted to evaluate the effect of treated rice straw using the four treatments (T1, T2, T7 and T8) selected from the first experiment and untreated rice straw (as control) on methane production and related fermentation parameters using in vitro gas production procedure. Results showed that all treatments significantly reduced total gas (102.33 vs. 51.17 to 67.67 mL), CH4 (30.21 vs. 13.46 to 18.10 mL) and CH4: VFA (0.71 vs. 0.38 to 0.46) compared to the control (P<0.05). Among the treatments, T8 showed the highest (55.45%) methane reduction compared to the control. All treatments had no effect on in vitro dry matter digestibility (IVDMD). Based on its high methane mitigation efficacy, T8 was selected to evaluate the effect of A. terreus (ATCC 74135) treated rice straw on in vivo methane production in goats. Eight male cross-bred Boer goats, fitted with rumen fistula, were used in the third experiment (Chapter 5). Rice straw treated using the protocol of T8 (as described in Chapters 3 and 4) was chosen as treatment and untreated rice straw as control in this feed trial. Methane production was estimated hourly for 12 hours (0800-2200h) per day using four open-circuit respiration chambers (~3,000 L). The measurement was repeated three times (triplicates) for each goat. Dry matter digestibility was determined using total fecal collection procedure and rumen liquor and blood samples were collected for VFA, microbial population and blood biochemical profile analysis. Result showed that daily methane production from goats fed on treated rice straw was reduced by 34.08% as compared to the control diet (13.27 vs. 20.13 L/day) (P<0.01). The above value increased to 42.36% if methane production was adjusted to per unit digestible DM intake (34.86 vs. 60.48 L). Dry matter digestibility for goats fed with treated rice straw diet improved (P<0.05) by 12.60% (80.0 vs. 69.9%). All treatments increased concentration of propionate (P<0.01) which led to a lower A/P ratio (P<0.01). This shift of VFA pathways to favor propionate production (a source of H2 sink) could partly explain for the lower methane production in the treatment group. The populations of total methanogens and Methanobacterials in goats fed treated rice straw diet were significantly lower than that of the control (P<0.05). In contrast, the populations of total bacteria and Ruminococcus albus (cellulolytic bacteria) increased significantly in goats fed treated rice straw diet (P<0.05). Blood biochemical profile data showed that cholesterol (P<0.05) and low density lipoprotein (LDL) (P<0.01) in goats in the treatment group were lower than those of the control. Results from this thesis showed that biological treatment using A. terreus (ATCC 74135) reduced the lignocellulose content thus improved the nutritive value of rice straw. The above fungal treatment produced lovastatin which effectively reduced methane production in vitro and in vivo (in goats) without negative effect to in vivo DM digestibility in goats. The reduction in populations of total methanogens and Methanobacteriales without negatively affecting other bacteria showed that the effect of lovastatin on methane production is specific on methanogens by inhibiting the activity of HMG-CoA reductase enzyme in the methanogens cell membrane synthesis pathway as reported in the literature. The increase in population of total bacteria and Ruminococcus albus (cellulolytic bacteria) further reaffirms the above. This thesis demonstrates that solid state fermentation using the appropriate fungus (e.g. A. terreus ATCC 74135) can improve nutritive value of agro-byproduct such as rice straw as ruminant feed and also reduce enteric methane production in ruminant livestock.